A unique ligand effect in Pt-based core–shell nanocubes to boost oxygen reduction electrocatalysis. Issue 39 (4th October 2021) - Wu, Xingqiao; Chen, XinKai; Li, Xiao; Yan, Yucong; Huang, Jingbo; Li, Junjie; Shen, Rong; Tian, He; Yang, Deren; Zhang, Hui
Abstract : A unique ligand effect mainly arising from the strong p–d orbital hybridization between Pt and Pb was demonstrated to play a key role in boosting the ORR properties of Pd3 Pb@Pt m Pb/C catalysts. Abstract : Pt-based core–shell nanocrystals are a fantastic catalyst to enhance the catalytic performance for the oxygen reduction reaction (ORR). Pursuing further enhancement in ORR properties requires an unconventional interaction between the components of a catalyst. Here Pb is selected to alloy with Pd cores and Pt shells for generating Pd3 Pb@Pt m Pb ( m = 3 and 4) nanocubes. Both nanocubes are much more active and stable for the ORR relative to commercial Pt/C, with Pd3 Pb@Pt3 Pb nanocubes being the better one. Specifically, Pd3 Pb@Pt3 Pb nanocubes achieved record-breaking mass (4.69 A mgPt −1 ) and specific (6.69 mA cm −2 ) activities in alkaline media, which are ∼40.4 and 25.3 times as high as those of commercial Pt/C, respectively. Furthermore, these nanocubes are highly stable with only 9.3% loss in mass activity after 10 000 cycles, as compared to a big decrease of 59.9% for commercial Pt/C. From geometrical phase analysis (GPA) combined with theoretical calculation data, the strain effect in such nanocubes contributes only ∼4% enhancement in ORR activity and the ligand effect is prominent due to the negligible lattice mismatch between Pd3 Pb and Pt m Pb. Besides electronic coupling between Pt and Pd, density functional theory (DFT) calculations show that the strong p–d orbital hybridization between Pt and Pb is critical to downshift the d-band center of Pt and dramatically boost the ORR activity.